The Impact of Globalization and Migration on Regional Hadith Studies - Abdullah Arafah; Ammar Makarim; Neni Nurlaela; Dadah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study examines the impact of globalization and migration patterns on the development of regional Hadith studies in the context of the contemporary Muslim world. As the second authoritative source in Islam, Hadith has undergone dynamic processes of transmission, interpretation, and adaptation that vary across different Muslim regions. Using a qualitative approach through literature review and comparative analysis, this research identifies three main patterns emerging as a result of globalization and migration: (1) methodological hybridization in Hadith studies that blends local traditions with transnational approaches; (2) the transformation of Hadith authority from a hierarchical-traditional model to a more complex global network; and (3) the recontextualization of Hadith to address specific socio-cultural challenges in various regions. The findings reveal that globalization and migration have facilitated the exchange of Hadith knowledge across regions, creating a new